A Valuable Attempt at Systematizing Contemporary Political Economy: A Review of Dutch Scholar Geert Reuten’s Textbook on Political Economy of Advanced Capitalism (World Marxist Review, 2025)
How to accept the economic role of state is a major issue that contemporary political economy—whether it is the socialist political economy with Chinese characteristics or the contemporary capitalist political economy stays to be addressed in its systemization process. One of the biggest changes in the capitalist economic system since Marx is the increasingly critical economic role played by the state. As early as in Anti-Dühring, Engels had already recognized this point. He proposed that the transformation of large production and transportation enterprises to state property had become a trend, which means that the state ultimately has to take on the leadership of production. After the emergence of Keynesian economics, this trend was also acknowledged by bourgeois economics. Since the 1980s, the various neoliberal economic theories have become popular and staunchly opposes the economic role of the state. However, the state’s role has only been partially weakened in specific areas, and overall, it continues to expand. Hence, the primary issue faced by contemporary political economy in its systematization is how to systematically summarize the state’s economic role and incorporate it into a comprehensive theoretical system. In most domestic textbooks, the role of the state is typically analyzed as a characteristic of the stage of state-monopoly capitalism. However, such analyses are relatively simple, and fail to adequately reflect the practice of economic intervention by advanced capitalist countries. Additionally, they are rather weak in terms of length. Furthermore, they do not fully integrate the laws of motion of capital accumulation analyzed by Marx, thus failing to truly propose an organic whole that combines the market mechanisms with the economic role of the state. Geert Reuten’s textbook has largely filled this gap. As a Marxist economist and a professor at the University of Amsterdam’s Faculty of Economics, Reuten has also served as a member of the Dutch parliament. In 2019, he published a textbook titled The Unity of Capitalist Economy and State: A Systematic-Dialectical Exposition of the Capitalist System. The distinctive feature of this textbook lies in its conscious application of systematic dialectics, integrating the theories of capitalist economy and capitalist state to form a theoretical system that is broader in content than Das Kapital and, simultaneously, strictly adheres to the systematic-dialectical method. Its experience is well worth our attention.